PENGARUH PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Wijaya, Andrea; Tjakrawala, F.X. Kurniawan (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to analyze the effect of profitability, leverage, and liquidity on firm value in companies in the primary consumer, non-primary consumer, healthcare, industrial, transportation & logistics sectors in the 2017-2021 period. The data collection carried out is quantitative in nature. The sample used is secondary data taken from the Indonesia Stock Exchange (IDX). In this study, the sample used was 300 samples from 97 companies using purposive sampling method. Data analysis using multiple linear regression method. Data was collected with the help of Microsoft Excel 2016 and processed using SPSS edition 21. The results in this study show that profitability (ROA) and leverage (DAR) have a positive and significant effect on firm value. While Liquidity (CR) has a positive but not significant effect on firm value.